Vascular anatomy of the splenic flexure, focusing on the accessory middle colic artery and vein. (17th November 2019) - Murono, K.; Miyake, H.; Hojo, D.; Nozawa, H.; Kawai, K.; Hata, K.; Tanaka, T.; Nishikawa, T.; Shuno, Y.; Sasaki, K.; Kaneko, M.; Emoto, S.; et al.
Abstract: Aim: Recently, the accessory middle colic artery (AMCA) has been recognized as the vessel that supplies blood to the splenic flexure. However, the positional relationship between the AMCA and inferior mesenteric vein (IMV) has not been evaluated. Herein, we aimed to evaluate the anatomy of the AMCA and the splenic flexure vein (SFV). Method: Two hundred and five patients with colorectal cancer who underwent enhanced CT preoperatively were enrolled in the present study. The locations of the AMCA and IMV were evaluated, focusing on the positional relationship between the vessels and pancreas – below the pancreas or to the dorsal side of the pancreas. Results: The AMCA was observed in 74 (36.1%) patients whereas the SFV was found in 177 (86.3%) patients. The left colic artery (LCA) was the major artery accompanying the SFV in 87 (42.4%) of patients. The AMCA accompanied the SFV in 65 (32.7%) patients. In 15 (7.8%) patients, no artery accompanied the SFV. The origin of the AMCA was located on the dorsal side of the pancreas in 15 (20.3%) of these 74 patients. Similarly, the destination of the IMV was located on the dorsal side of the pancreas in 65 (31.7%) of patients. Conclusion: The SFV was observed in most patients, and the LCA or AMCA was the common accompanying artery. In some patients these vessels were located on the dorsal side of the pancreas and not below it. Preoperative evaluation of this anatomy may be beneficial for lymph node dissection during left‐sided hemicolectomy.